2002
DOI: 10.1269/jrr.43.s213
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeletal and Functional Changes in Bioreactor Assembled Thyroid Tissue Organoids Exposed to Gamma Radiation

Abstract: Fischer rat thyroid cells were grown under low-shear stress in a bioreactor to a stage of organization composed of integrated follicles resembling small thyroid glands prior to exposure to 3 Gray-gamma radiation. Bioreactor tissues and controls (both irradiated and non-irradiated) were harvested at 24, 48, 96 and 144 hours post-exposure. Tissue samples were fixed and fluorescently labeled for actin and microtubules. Tissues were assessed for changes in cytoskeletal components induced by radiation and quantifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…Many round-shaped melanoma cells, being probably pre-apoptotic, were detected 6 h after proton irradiation. Similar changes of cellular morphology were already reported for different cell lines such as Chinese hamster V79 and FRTL-5 cells, after being exposed to ionizing irradiations (Aoki et al, 2000;Green et al, 2002). All these morphological changes were followed by the significant reduction of the cell number.…”
Section: Resultssupporting
confidence: 83%
“…Many round-shaped melanoma cells, being probably pre-apoptotic, were detected 6 h after proton irradiation. Similar changes of cellular morphology were already reported for different cell lines such as Chinese hamster V79 and FRTL-5 cells, after being exposed to ionizing irradiations (Aoki et al, 2000;Green et al, 2002). All these morphological changes were followed by the significant reduction of the cell number.…”
Section: Resultssupporting
confidence: 83%
“…However, the partial recovery detected may be due to the short time left for the cell to regenerate. This had been demonstrated by Green et al [48] who reported regeneration of follicular cells immediately and may be more effective with Vit.E for two weeks after exposure.…”
Section: Discussionmentioning
confidence: 63%
“…The scan was analyzed (RIT-113 Image analysis software) and field uniformity determined to be 97.3%, and 100% within the 20x20 cm field used for typical exposure of tissue culture/bioreactor vessels. The dose was delivered as acute single fractions at a dose rate of approximately 50 cGy/minute (Green et al, 2002a(Green et al, & 2002b.…”
Section: Sources Of Radiationmentioning
confidence: 99%
“…These procedures are/were performed according to standard methods (Green et al, 1995(Green et al, , 1997(Green et al, , 2001a(Green et al, , 2001b(Green et al, , 2002b. The bioreactor grown tissue was removed, covered with cryoprotectant and stored frozen.…”
Section: Immunocytochemical Protein Analysismentioning
confidence: 99%
See 1 more Smart Citation